Moment-rotation model of endplate blind bolted joints with CFST column. (January 2021) - Fan, Junchao; Zhao, Junhai; Gao, Weiqi
Abstract: The moment-rotation curves can directly reflect the performance of H-shaped beam to concrete filled steel tube (CFST) column joints, which should be fully considered in structure analysis and design of such joints. However, the current determination of moment-rotation curves is mainly fitting results of experiments or simulations, which results considerable consumption of human and material resources. Hence, this paper proposes a new three-parameter exponential model for this type of joint to forecast the moment-rotation relation curve. Considering possible failure modes, a calculation method of ultimate bending moment for joints is proposed. An analysis model of initial rotational stiffness for joints is established according to component method. Based on the research results of this paper, the ultimate bending moment and initial rotational stiffness can be calculated straight by measurement factors and material properties. The values of the shape parameter for two kinds of the joint are derived by fitting the existing experimental data. Based on the established prediction model of moment-rotation, an accurate calculation method of ultimate bending moment, and analysis model of initial rotational stiffness, the prediction results are in good agreement with experimental results according to the comparison. The established moment-rotation model may be applied to the design of composite frames to predict the behavior of the joint with endplate and blind bolts simply and accurately. Moreover, it can save the workload of experiments and simulations. Graphical abstract: In our work, a new three-parameter exponential model is established for two common types of the endplate blind bolted joint to predict the moment-rotation relation. Meanwhile, the calculation method of ultimate moment resistance is proposed and the analysis model of initial rotational stiffness is established. Moreover, the comparison with experiments shows that the proposed method and established models have high accuracy. Unlabelled Image Highlights: A three-parameter exponential model for M - θ of blind bolted joints is established. Calculation method for ultimate moment resistance of joints is proposed. Analysis models for rotational stiffness of blind bolted joints are proposed. Compared with experiments, proposed method and established models have high accuracy. Analysis models are suitable for two usual CFST joints with endplate and blind bolts.